2020
DOI: 10.1002/jbm4.10380
|View full text |Cite
|
Sign up to set email alerts
|

LGRs in Skeletal Tissues: An Emerging Role for Wnt‐Associated Adult Stem Cell Markers in Bone

Abstract: Leucine-rich repeat-containing G protein-coupled receptors (LGRs) are adult stem cell markers that have been described across various stem cell niches, and expression of LGRs and their corresponding ligands (R-spondins) has now been reported in multiple bonespecific cell types. The skeleton harbors elusive somatic stem cell populations that are exceedingly compartment-specific and under tight regulation from various signaling pathways. Skeletal progenitors give rise to multiple tissues during development and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 96 publications
(161 reference statements)
0
19
0
Order By: Relevance
“…The cell type was located around the chondrocytes within cartilage in our Visium ST (Figure 2g) and could be identified by the expression of the marker gene COL12A1 in the human protein atlas (Figure S5c). Among the marker genes for PC-fibro, we detected bone development genes LGR4 and LGR6 (Doherty and Sanjay 2020) (Figure S5b). PC-fibro, which express standard fibroblasts markers, is unique in expressing genes relevant for bone development, placing these cells into a trajectory from adventitial fibroblasts to chondrocytes (Figure S5 d, e).…”
Section: Resultsmentioning
confidence: 99%
“…The cell type was located around the chondrocytes within cartilage in our Visium ST (Figure 2g) and could be identified by the expression of the marker gene COL12A1 in the human protein atlas (Figure S5c). Among the marker genes for PC-fibro, we detected bone development genes LGR4 and LGR6 (Doherty and Sanjay 2020) (Figure S5b). PC-fibro, which express standard fibroblasts markers, is unique in expressing genes relevant for bone development, placing these cells into a trajectory from adventitial fibroblasts to chondrocytes (Figure S5 d, e).…”
Section: Resultsmentioning
confidence: 99%
“…These receptors bind to R-spondins (RSPOs), causing the formation of the LGR-RSPO-ZNRF/RNF43 complex. This leads to the sequestration of ZNF/RNF43, which causes an increase in membrane-available FDZs, since the transmembrane ubiquitin ligases ZNF/RNF43 are responsible for degrading them [ 31 ]. In addition to this agonistic effect on the Wnt pathway, LGR is a target gene of the Wnt pathway, which will produce a positive feedback loop [ 31 ].…”
Section: Co-receptorsmentioning
confidence: 99%
“…This leads to the sequestration of ZNF/RNF43, which causes an increase in membrane-available FDZs, since the transmembrane ubiquitin ligases ZNF/RNF43 are responsible for degrading them [ 31 ]. In addition to this agonistic effect on the Wnt pathway, LGR is a target gene of the Wnt pathway, which will produce a positive feedback loop [ 31 ]. It has also been reported that LGR proteins mark different adult stem cells and play a very important role in defining progenitor and stem cell behavior [ 31 , 181 , 182 ].…”
Section: Co-receptorsmentioning
confidence: 99%
See 2 more Smart Citations